Gene Therapy in Movement Disorders: A Systematic Review of Ongoing and Completed Clinical Trials - Merola, Aristide; Kobayashi, Noelle; Romagnolo, Alberto; Wright, Brenton A.; Artusi, Carlo Alberto; Imbalzano, Gabriele; Litvan, Irene; Van Laar, Amber D.; Bankiewicz, Krystof (Frontiers in Neurology, 2021)
Introduction: We sought to provide an overview of the published and currently ongoing movement disorders clinical trials employing gene therapy, defined as a technology aiming to modulate the expression of one or more genes to achieve a therapeutic benefit. Methods: We systematically reviewed movement disorders gene therapy clinical trials from PubMed and ClinicalTrials.gov using a searching strategy that included Parkinson disease (PD), Huntington disease (HD), amino acid decarboxylase (AADC) deficiency, multiple system atrophy (MSA), progressive supranuclear palsy (PSP), dystonia, tremor, ataxia, and other movement disorders. Data extracted included study characteristics, investigational product, route of administration, safety/tolerability, motor endpoints, and secondary outcomes (i.e., neuroimaging, biomarkers). Results: We identified a total of 46 studies focusing on PD (21 published and 9 ongoing), HD (2 published and 5 ongoing), AADC deficiency (4 published and 2 ongoing), MSA (2 ongoing), and PSP (1 ongoing). In PD, intraparenchymal infusion of viral vector-mediated gene therapies demonstrated to be safe and showed promising preliminary data in trials aiming at restoring the synthesis of dopamine, enhancing the production of neurotrophic factors, or modifying the functional interaction between different nodes of the basal ganglia. In HD, monthly intrathecal delivery of an antisense oligonucleotide (ASO) targeting the huntingtin protein (HTT) mRNA proved to be safe and tolerable, and demonstrated a dose-dependent reduction of the cerebrospinal fluid levels of mutated HTT, while a small phase-I study testing implantable capsules of cells engineered to synthesize ciliary neurotrophic factor failed to show consistent drug delivery. In AADC deficiency, gene replacement studies demonstrated to be relatively safe in restoring catecholamine and serotonin synthesis, with promising outcomes. Ongoing movement disorders clinical trials are focusing on a variety of gene therapy approaches including alternative viral vector serotypes, novel recombinant genes, novel delivery techniques, and ASOs for the treatment of HD, MSA, and distinct subtypes of PD (LRRK2 mutation or GBA1 mutation carriers). Conclusion: Initial phase-I and -II studies tested the safety and feasibility of gene therapy in PD, HD, and AADC deficiency. The ongoing generation of clinical trials aims to test the efficacy of these approaches and explore additional applications for gene therapy in movement disorders.